2021
DOI: 10.4103/eus-d-20-00198
|View full text |Cite
|
Sign up to set email alerts
|

Wet- versus dry-suction techniques for EUS-FNA of solid lesions: A systematic review and meta-analysis

Abstract: The optimal sampling techniques for EUS-FNA remain unclear and have not been standardized. To improve diagnostic accuracy, suction techniques for EUS-FNA have been developed and are widely used among endoscopists. The aim of this study was to compare wet-suction and dry-suction EUS-FNA techniques for sampling solid lesions. We performed a comprehensive literature search of major databases (from inception to June 2020) to identify prospective studies comparing wet-suction EUS-FNA and dry-suction EUS-FNA. Specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Blood contamination in paraffin sections can significantly affect the result of pathological diagnosis, and current studies on the effect of heparin use in puncture are controversial [ 6 , 29 ]. A recent meta-analysis demonstrated that heparin use had no significant effect on blood contamination in paraffin sections [ 8 ]. In this context, we found that there was a statistically significant difference in the blood contamination between the two groups in the first puncture, with less blood contamination in the Experimental group than in the Control group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood contamination in paraffin sections can significantly affect the result of pathological diagnosis, and current studies on the effect of heparin use in puncture are controversial [ 6 , 29 ]. A recent meta-analysis demonstrated that heparin use had no significant effect on blood contamination in paraffin sections [ 8 ]. In this context, we found that there was a statistically significant difference in the blood contamination between the two groups in the first puncture, with less blood contamination in the Experimental group than in the Control group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…At present, multiple techniques have been developed to improve the quality of puncture specimens, such as negative micro-pressure, fanning puncture and wet tap [ 4 ], but the effect is unsatisfactory. Previous studies pointed out that wet-heparinized suction for biopsy of a peritoneal lesion could increase the sample volume and reduce blood contamination [ 5 8 ]. Due to the distinct difference between the histological characteristics of peritoneal and mediastinal masses [ 9 ], this technique is poorly investigated in studies on mediastinal masses, especially on mediastinal lymph node.…”
Section: Introductionmentioning
confidence: 99%
“…There have been two meta-analyses of suction techniques. Ramai et al compared wet and dry suction, and wet suction has shown advantages in terms of specimen adequacy (pooled OR: 3.18, 95% CI: 1.82-5.54) [49]. Wang et al showed that the slow-pull technique was better than the standard method in terms of core tissue acquisition (pooled OR: 1.91, 95% CI: 1.11-3.26), blood contamination (pooled OR: 1.93, 95% CI: 1.29-2.87), and diagnostic accuracy (pooled OR: 1.60, 95% CI: 1.14-2.26) [50].…”
Section: Door-knocking Method Fanning Technique and Suction Techniquesmentioning
confidence: 99%
“…Suction is commonly used to obtain adequate samples, but it may damage cellular structures and contaminate the sample with blood, clouding cytologic interpretation[ 27 ]. Compared with dry suction, wet suction has better sample adequacy and higher diagnostic accuracy without increasing blood contamination[ 28 , 29 ].…”
Section: Suction Slow-pull or Non-suctionmentioning
confidence: 99%